THU0586 Methotrexate drug survival and adverse effects in patients with juvenile idiopathic arthritis. (12th June 2018) - Kearsley-Fleet, L.; Vicente González, L.; Steinke, D.; Davies, R.; De Cock, D.; Baildam, E.; Beresford, M.W.; Foster, H.E.; Southwood, T.R.; Thomson, W.; Hyrich, K.L.
Abstract : Background: Methotrexate is usually the first-line disease modifying anti-rheumatic drug (DMARD) for patients with juvenile idiopathic arthritis (JIA), due to its efficacy, the low-cost and favourable safety profile in patients. However, one of the most reported adverse effects of interest (AEIs) of methotrexate is nausea. Objectives: The objectives of this analysis were to (i) calculate methotrexate monotherapy drug survival, (ii) describe AEIs over the first two years of treatment, and (iii) investigate factors associated with occurrence of AEIs among children with JIA. Methods: Patients with all forms of JIA starting methotrexate monotherapy from both the UK BSPAR Etanercept Cohort Study (BSPAR-ETN) and Biologics for Children with Rheumatic Diseases study (BCRD) were included. Patient characteristics and anti-rheumatic therapy details were collected at treatment start. Follow-up data were collected at six months, one year, and annually thereafter, on changes to anti-rheumatic therapy and any adverse events. AEIs were grouped into gastrointestinal-related (nausea, vomiting, abdominal pain), raised liver enzymes, leukopenia, drug hypersensitivity (injection site reaction), rash, needle phobia, and any other event leading to permanent discontinuation of methotrexate. All person time was included from methotrexate start date until first methotrexate stop date, start of biologic therapy, last patient follow-up date, or 30-June-2017 (study cut-off date), whichever came first. Survival analysis was used to assess time on methotrexate monotherapy and time to first AEI on methotrexate monotherapy. Multivariable logistic regression was used to assess baseline characteristics associated with experiencing an AEI, and a gastrointestinal-related AEI only. Results: Of 505 patients starting methotrexate between 01-January-2010 and 30-June-2015 (to allow at least two years of follow-up for all children), median time on monotherapy was 1.5 years (IQR 0.7, 2.3). At two years, 274 (54%) patients were no longer on methotrexate monotherapy. Reasons included: inefficacy (n=174; 64%) mostly due to start of biologic therapy (n=161), adverse events (n=54; 20%), remission (n=24; 9%), and patient/family decision (n=9; 3%). Within the first two years of methotrexate monotherapy, 181 (36%) patients experienced at least one AEI; the most common were gastrointestinal problems (n=116; 53%) and liver enzyme abnormalities (n=42; 19%). No clinical factors were associated with occurrence of any AEI, nor a gastrointestinal-related AEI. Conclusions: After two years, over half of the patients were no longer on methotrexate monotherapy, whilst one-third experienced at least one AEI, most commonly gastrointestinal-related problems. Further research focussing on identifying which children will respond and/or experience an AEI with methotrexate is crucial, such that AEIs can be minimised or prevented and treatment benefit maximised. Disclosure of Interest: None declared